Fixation of Olecranon Fractures Using a Hybrid Intramedullary Screw and Tension Band Construct - Kaitlin Rush; John Fisher; Neil Jain; Caleb Gottlich; Cyrus Caroom (Advances in Orthopedics)
Introduction. Olecranon fractures are common injuries that require surgical intervention for optimal outcomes. Various fixation methods have been described in the literature, including the use of intramedullary proximal ulna screws in combination with tension band augmentation. Limited research has compared this hybrid technique to other established methods of fixation. This study compared complication and reoperation rates between multiple groups. Methods. A retrospective review was conducted on patients with olecranon fractures who underwent internal fixation at a level 1 trauma center between January 1st, 2013, and April 22nd, 2023. Data was collected using CPT codes, and patients were categorized into five groups based on the method of fixation received: no implant, tension band only, locking olecranon plate, intramedullary screw and tension band hybrid, and others. Variables such as patient demographics, Mayo fracture classification, open vs. closed injury, implant type, reoperation rates, and postoperative complications were recorded. Results. A total of 217 patients were included in the study. No difference was found with implant choice and reoperation rate (p=0.461). There was a significant difference found with reoperation and fracture type (p=0.027) and open fracture (p=0.002). Conclusion. The primary findings of this study indicate no significant difference in implant choice and reoperation rates among the various fixation methods used for olecranon fractures. These findings suggest that the hybrid fixation technique, utilizing intramedullary proximal ulna screws in combination with tension band augmentation, is a viable and comparable treatment option when evaluated against other well-documented methods of fixation. This study also reiterates that severity of initial injury is often the most important factor related to poorer outcomes. Further discussion and analysis of the data will provide a comprehensive understanding of implications and recommendations for olecranon fracture fixation.